THE STUDY OF METAPHOR - Kassymova, A.K. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
This article includes the meanings of metaphor, its classification, variety. To this day, there is no exact definition about the metaphor, the proof of this is presented in the article in the form of different statements by different scientists, writers who write about the metaphor.
Keywords: metaphor; classification of metaphor; varities of metaphor